Advertising and disclosure: Do firms time advertising during disclosure periods? - WANG, Yin (Institutional Knowledge at Singapore Management University, 2018)
Using a large sample of monthly advertising data, I examine whether U.S. firms use advertisingstrategically during disclosure periods. I find that firms schedule some advertising to appeararound their SEC 10-K, 10-Q filings and around their earnings announcements, consistent withadvertising being used to increase visibility and attract investor attention during disclosureperiods. This effect is stronger for firms reporting good news, for firms with high individualinvestor ownership, for firms in the retail industry, and for young firms. In addition, firmsincrease their advertising through media with broad target audiences and through business-toconsumer media around their disclosures (i.e. SEC 10-K, 10-Q filings and earningsannouncements). Furthermore, I use the SEC acceleration filing rule as an exogenous shock tothe timing of firms’ mandatory disclosures. Using a Difference-in-Difference design, I find thatadvertising expenditures co-move with the change in timing of the 10-K filings. Parallel trendanalysis and falsification test results further validate this causal inference that firms’ mandatorydisclosures cause the timing of firms’ advertising. Finally, the results also suggest that firmswith high information asymmetry and lower market liquidity advertise more when they havedisclosures. Taken together, the findings provide new evidence about the real effects ofdisclosure on firm-specific investment, showing that firms consider disclosure timing whenmaking advertising investment decisions.